How attachment influences users’ willingness to donate to content creators in social media: A socio-technical systems perspective - Wan, Jinlin; Lu, Yaobin; Wang, Bin; Zhao, Ling (Information & management, 2017)
As a relatively new behavior, donation to content creators in social media has become very popular in the last few years. Different from traditional donation to nonprofit organization or victims, donation to content creators in social media has received little attention from academic researchers. On the basis of the socio-technical systems framework and attachment theory, this study develops a model to investigate the effects of social and technological factors on users’ donation behavior. Our results indicate that donation intention is determined by the emotional attachment to the content creator and functional dependence on social media, which are influenced by both social factors (identification, interaction, and information value) and technical factors (sociability and personalization).